New data on the construction and meaning of the Shengavit settlement wall - Simonyan, Hakob; Rothman, Mitchell S (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Shengavit is a site of the Kura-Araxes cultural tradition, which radiocarbon dates and pottery style indicate spans its second phase, the KA2, from 2900 to 2500 BC. It also documents the transition to the Early Kurgan Period. The six-hectare site gives indications that it was a center for this time and place. Unlike the societies of the KA1 of 3500-3000 BC, we recovered evidence of the development of increased societal complexity while retaining an egalitarian symbolism. One of these signs is the construction of a massive stone wall with watchtowers, which we think surrounded the top of a bluff over the Hrazdan River. The effort needed to plan and recruit the labor to construct this wall, along with a profusion of large grain storage pits greater in volume than needed by residents of the site, point to the origin of some coordination mechanisms at the site. Still, some have questioned the Kura-Araxes date for the settlement wall. We discuss these issues and present new findings about the wall in this contribution, made in honor of Ruben Badalyan, who himself has done so much to promote our knowledge of the Kura-Araxes in Armenia.